1997
DOI: 10.1007/s004210050170
|View full text |Cite
|
Sign up to set email alerts
|

Trained versus untrained men: different immediate post-exercise responses of pituitary adrenal axis

Abstract: The hypothalamo-pituitary-adrenal axis is involved throughout the exercise-recovery cycle. Nevertheless, differences in hormone responses during early recovery between sedentary and endurance trained subjects are not well known. The aim of this preliminary study was to monitor plasma cortisol and adrenocorticotropic hormone (ACTH) concentrations both during and after the end of running exercise performed by four endurance trained adults (marathon men) compared to four sedentary subjects. Two parameters, i.e. i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
50
0
9

Year Published

2000
2000
2012
2012

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(62 citation statements)
references
References 32 publications
3
50
0
9
Order By: Relevance
“…More specifically, when sedentary and healthy ET men are compared in resting, unchallenged conditions, no difference in HPA axis activity is seen. Indeed, we and others have previously reported normal plasma cortisol values with preserved nycthemeral cortisol rhythm in ET men compared with sedentary subjects (2,3), as well as normal 24 h UFC after a day with no training (4). By contrast, when the HPA axis is challenged, results from ET men differ from those of sedentary men.…”
Section: Introductionmentioning
confidence: 60%
See 1 more Smart Citation
“…More specifically, when sedentary and healthy ET men are compared in resting, unchallenged conditions, no difference in HPA axis activity is seen. Indeed, we and others have previously reported normal plasma cortisol values with preserved nycthemeral cortisol rhythm in ET men compared with sedentary subjects (2,3), as well as normal 24 h UFC after a day with no training (4). By contrast, when the HPA axis is challenged, results from ET men differ from those of sedentary men.…”
Section: Introductionmentioning
confidence: 60%
“…By contrast, when the HPA axis is challenged, results from ET men differ from those of sedentary men. For example, after an exercise-induced cortisol increase, the subsequent stimulation exerted by a meal does not elicit a rise of cortisol levels in sedentary men, whereas in ET men a marked cortisol increase occurs (3). These findings suggesting a decreased sensitivity to glucocorticoid negative feedback in healthy ET men may reflect allostatic modifications of the HPA axis due to repeated exercise-induced HPA axis activation (5).…”
Section: Introductionmentioning
confidence: 87%
“…Accordingly, morning plasma cortisol concentration and 24 h urinary free cortisol (UFC) excretion in resting endurance-trained men are similar to those of age-matched sedentary subjects (Kern et al 1995;Duclos et al 1997;Gouarne et al 2005). Since UFC represents an integrated measure of the 24 h cortisol secretion, this is in accordance with the previously reported normal diurnal HPA axis rhythm in endurance-trained men (Duclos et al 1997(Duclos et al , 2007. Finally, endurance-trained men maintain the seasonal rhythmicity of cortisol excretion; as in sedentary men the highest concentrations of urinary cortisol, morning plasma cortisol and saliva cortisol are observed during autumn and winter compared with spring and summer (Gouarne et al 2005).…”
Section: Biochemistry and Hormones Biochemistrymentioning
confidence: 85%
“…For example, the HPA adaptation to normal training is characterised by increased ACTH/cortisol ratio only during exercise recovery (due to decreased pituitary sensitivity to cortisol) (Lehmann et al 1993b;Duclos et al 1997Duclos et al , 1998, and by modulation REVISION : Consensus Statement "Overtraining" (17-07-2012) 10 of tissue sensitivity to glucocorticoids (Duclos et al 1999(Duclos et al , 2003). However, it should be emphasized that during a resting day, in endurance-trained athletes 24 h cortisol secretion under non-exercising conditions is normal Duclos et al 1999Duclos et al , 2003.…”
Section: Biochemistry and Hormones Biochemistrymentioning
confidence: 99%
“…[63,181] The mechanism for the decline apto decline with training, [77,193] apparently as a result pears to be hypothalamic in origin, possibly involvof altered ACTH functioning. [193,194] ing opioids, prolactin, CRH, or gonadotrophic horStudies have reported that resting concentrations mone-releasing hormone. [58] In contrast to the anof leptin may decline with endurance or resistance drogens, we know little about the estrogen response training.…”
Section: Exercise-induced Modifications 6 Exercise-induced Changes Omentioning
confidence: 99%